AGE-RELATED DIFFERENCES ON THE ENHANCEMENT OF NON- DOMINANT HAND MOTOR FUNCTION AFTER PARALLEL INTERVENTION OF ANODAL TDCS AND MOTOR TASK: A TMS STUDY. Issue 10 (10th June 2013) - Kakoura, Eleni; Baka, Katerina; Katsoulaki, Marianna; Dang, Mai; Fotiou, Stella; Nowicky, Alexander
Abstract : Background: Healthy ageing is accompanied by cognitive and functional deficits which result in decreased ability to respond quickly and accurately to different stimuli. Whilst a general decline is observed in manual dexterity and hand motor function of older adults affecting their daily life, learning ability is almost completely intact. NIBS techniques such as tDCS has been found to have effective results by enhancing cortical excitability and motor learning and function in the younger adults. The purpose of this study was to further investigate any improvements in non-dominant hand motor function, examining the effects of tDCS alongside a motor skill rehabilitation task (MSRT) in motor learning in the ageing brain, focusing on any age-related differences. Methods: Thirty-two healthy subjects (YAs: n=20, mean age= 24.4± 2.03; OAs: n=12, mean age= 64.3± 9.56) participated in this double-blinded, sham-controlled study, undertaking a single session of either anodal or sham tDCS on the non- dominant M1. The MSRT was carried out as an outcome measure to investigate any changes in hand function, speed and accuracy, with TPR scores indicating level of MSRT performance. TMS was used to detect any changes in cortical excitability of the non-dominant hemisphere, measuring the MEPs of the non-dominant APB. The cortical excitability assessment through paired-pulse TMS was based on Kujirai protocol, measuring the SICI/F) and the LICI/F at predetermined delays. At baseline, behavioural functional tasks were carried out to evaluate speed and accuracy of the participant before intervention. The statistical data analysis was carried out using mixed analysis of ANOVA (P<0.05). Results: There were significant differences between the type of tDCS application (anodal versus sham) regarding the APB MEP responses detected by TMS (P= 0.03). Also, a significant effect of age was found on overall TPR scores with younger individuals obtaining lower scores than the older (P =0.003), indicating better MSRT performance. Another outcome was the significant improvement level of the MSRT for all groups across the time intervals (P<0.001). However, no significant age- related differences found concerning the overall facilitation or inhibition. Conclusion: Though some findings did not reach at a statistical significance level, a-tDCS coupled with MSRT did ameliorate motor performance and therefore suggests that brain stimulation can enhance motor function in the ageing brain, facilitating motor learning through a-tDCS. Further research into neurorehabilitation can continue to contribute to the understanding of normal ageing and confirm the positive impacts of a-tDCS alongside motor tasks for ageing individuals as well as its potential as a poststroke intervention. Additionally this research could be used further as a post-traumatic sport rehabilitation because of the impact on the healthy younger groups.